Sociological Aspects of Judges in Granting Applications for Marriage Dispensation (Study of Determination Number: 0038/Pdt.P/2014/PA.Pt) - Arina Hukmu Adila (Walisongo Law Review (Walrev), 2020)
Many children have a pregnancy out of wedlock. Many factors make the parents marry off their underage children who are pregnant out of wedlock, by applying for matrimonial dispensation to the Religious Courts. Law Number 1 Year 1974 on Marriage has set a minimum age limit for men and women to marry with age and psychological maturity considerations, for the realization of the purpose of the marriage. This study uses a juridical-empirical method, which will see the Religious Courts as the authorized institution, having particular considerations in granting marriage dispensation applications in order to fulfill the rights of the people and to preserve the order of life in the community.[]Banyak terjadi anak-anak mengalami kehamilan di luar nikah akibat dari pergaulan yang terlalu bebas antara laki-laki dan perempuan. Banyak faktor yang membuat orang tua menikahkan anaknya yang masih di bawah umur yang hamil di luar nikah, yakni dengan mengajukan permohonan dispensasi kawin ke Pengadilan Agama. Undang-undang Nomor 1 Tahun 1974 tentang Perkawinan telah menentukan batas usia minimum bagi laki-laki dan perempuan untuk menikah dengan pertimbangan kematangan usia dan psikologis, demi terwujudnya tujuan pernikahan tersebut. Penelitian ini menggunakan metode yuridis-empiris, yang akan melihat Pengadilan Agama sebagai lembaga yang  berwenang, memiliki pertimbangan-pertimbangan tertentu dalam mengabulkan permohonan dispensasi kawin dengan tujuan untuk memenuhi hak-hak masyarakat.